2000
DOI: 10.1086/313298
|View full text |Cite
|
Sign up to set email alerts
|

A Recalibration of IUE NEWSIPS Low‐Dispersion Data

Abstract: While the low dispersion IUE NEWSIPS data products represent a significant improvement over original IUE SIPS data, they still contain serious systematic effects which compromise their utility for certain applications. We show that NEWSIPS low resolution data are internally consistent to only 10-15% at best, with the majority of the problem due to time dependent systematic effects. In addition, the NEWSIPS flux calibration is shown to be inconsistent by nearly 10%.We examine the origin of these problems and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 11 publications
2
81
0
Order By: Relevance
“…The individual IUE observations were downloaded from the MAST archive at Space Telescope Science Institute (STScI) and were co-added to produce a single spectrum from 1150 to 3225 Å with a resolution of approximately 400. The calibration of these spectra was improved using the results of Massa & Fitzpatrick (2000), who found that the signal-to-noise ratio of IUE low-dispersion data could be significantly improved over that provided in the IUE archive.…”
Section: Ultraviolet Spectramentioning
confidence: 99%
“…The individual IUE observations were downloaded from the MAST archive at Space Telescope Science Institute (STScI) and were co-added to produce a single spectrum from 1150 to 3225 Å with a resolution of approximately 400. The calibration of these spectra was improved using the results of Massa & Fitzpatrick (2000), who found that the signal-to-noise ratio of IUE low-dispersion data could be significantly improved over that provided in the IUE archive.…”
Section: Ultraviolet Spectramentioning
confidence: 99%
“…In this paper, we present the results of our analysis of three of these spectra. Massa & Fitzpatrick (2000) have shown that the absolute flux calibration of the NEWSIPS low-dispersion data was inconsistent with its reference model and subject to time-dependent systematic effects, which together amount to as much as 10%-15%. Therefore, in order to correct the data and optimize the signal-to-noise ratio, we used the IDL programs that apply Massa-Fitzpatrick corrections to the lowdispersion IUE data.…”
Section: Observationsmentioning
confidence: 99%
“…The spectrum was absolutely normalized at 21 observed photometric points between 0.38 and 12 µm, as described by Cohen et al (2003). Nineteen empirical UV spectra (17 SW, 2 LW) were recalibrated (Massa & Fitzpatrick 2000) and combined using the overlap. From 0.335 to 160 µm the spectrum is the normalized photosphere.…”
Section: The Input Stellar Spectramentioning
confidence: 99%